What did Plato think of Solon? - Giammarco, Maria Carla (Montesquieu.it, 2021)
Solon’s reform in Athens (early 6th century BC) is the subject of wide discussions: an organic constitutional reform (politeia) or individual sectoral laws? Plato’s testimony has received limited attention from critics, who are mainly focused on the passages from Charmides and Timaeus, alluding to the kinship (syngheneia) between the two. Indeed, the philosopher is not generous with details and does not explicitly describe the ‘constitution of Solon’; however, a thorough examination of the references – in as chronological an order as was possible – has revealed clear data and an evolving thought. Unlike Aristotle and Herodotus, Plato outlines a somewhat reductive portrait of Solon as a poet and wise man; but, as a legislator, in his dialogues of maturity Plato repeatedly counts Solon among the ‘greats’ of the past, those who, through reforming the politeia, have fixed their State bodies identity. Finally, in the Laws, his last work, Plato shows his expertise on some of the Solonic laws and expresses a mild appreciation for their author. On the whole, while Plato’s testimony does not contradict Aristotle’s much more thorough and favorable one, neither does it coincide with it: on the person of the legislator, as well as on the thorny questions connected to his ‘constitution’– such as the ideology of the ‘mixed constitution’ and that of the Athenian patrios politeia – the positions of the two philosophers prove to be distant, both in the conceptual framework and in the political judgment.